Sistem Controling Engine Menggunakan Fingerprint Berbasis Arduino - Nur Hidayat Syukron (Department of Science and Technology Ibrahimy University, 2019)
The growth of motorcycles at this time is very fast. The case of motorcycle theft is still often the case, this happens because there is still a lack of security systems that exist in motor vehicles that only use the ignition key. In addition, the lack of human control systems are still often missed. Motorcycles are the main transportation at this time, so it needs to be made bicycle security system. Security is done in the form of a system with fingerprints in anticipation of the frequent mode of motorcycle theft, which can access by using fingerprints are certain people whose fingerprint data has been programmed into the system, so that the motorcycle can not live without the match between the fingerprint which is detected by the sensor by fingerprint.